2020
DOI: 10.1249/mss.0000000000002322
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Exercise Training to Improve Exercise Capacity in Obese Individuals

Abstract: Introduction Combining exercise training with hypoxic exposure has been recently proposed as a new therapeutic strategy to improve health status of obese individuals. Whether hypoxic exercise training (HET) provides greater benefits regarding body composition and cardiometabolic parameters than normoxic exercise training (NET) remains, however, unclear. We hypothesized that HET would induce greater improvement in exercise capacity and health status than NET in overweight and obese individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…4,92 Following these initial observations, several recent studies compared the effect of exercise training in hypoxia versus normoxia in individuals with obesity. Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,92 Following these initial observations, several recent studies compared the effect of exercise training in hypoxia versus normoxia in individuals with obesity. Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
“…Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training. Similarly, only two 99,101 out of six studies 23,91,[97][98][99]101 that investigated exercise performance following hypoxic exercise training in individuals with obesity reported greater improvement compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
“…Perhaps a greater training dose (i.e., higher intensity and/or longer training duration) may be required in normotensive individuals (as recruited here) to positively impact on exercise capacity and cardio-metabolic health when in hypoxia compared to normoxia (Navarrete-Opazo and Mitchell, 2014). That said, despite greater improvement in exercise tolerance, HC (hypobaric hypoxia with a target SpO 2 of 80%) thrice weekly for 8 weeks was not associated with larger improvement in either body composition or vascular and metabolic functions in overweight-to-obese individuals compared to normoxic equivalent (Chacaroun et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Recently there has been an increased interest in the use of hypoxic conditioning (HC) as a strategy for promoting indicators of health and weight loss in individuals with obesity (Hobbins et al 2017;Ramos-Campo et al 2019). In comparison to normoxic constant-load exercise training programmes (e.g., 60-90 min walking/running, cycling or cross-training at 60-75% maximal oxygen uptake [V O 2max ] or heart rate [HR max ]), HC with an FiO 2 in the range 13-16.5% for 4-8 weeks has been shown to elicit greater reductions in body mass and fat mass (Netzer et al 2008;Wiesner et al 2009), along with improvements in blood glucose concentrations (Haufe et al 2008;De Groote et al 2018), blood pressure (Kong et al 2014) and exercise capacity (Chacaroun et al 2020). Comparatively, perceptual responses and exercise-related sensations associated with this type of training have so far been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…In a review study of the circulatory and metabolic responses to hypoxia in humans [18], the authors presented studies supporting hypoxia as a possible treatment for obesity [19,20]. One study found that combining hypoxic exposure with exercise training may provide some additional health benefits, albeit limited, to standard normoxic exercise training for obese individuals [21]. In a review article involving obese individuals, there was little evidence that hypoxia had superior health effects (i.e., lower glucose, insulin, cholesterol, HDL, triglycerides, heart rate, blood pressure, body mass index, and body weight) compared with normoxia [22].…”
Section: Discussionmentioning
confidence: 99%